THE ASSESSMENT-FOR-LEARNING TO ENHANCE SPEAKING FLUENCY AT THE FOURTH SEMESTER STUDENTS OF MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Muh. Nahwi Al-Bukhari W. Simbala; Eny Syatriana; Firman (Journal of Language Testing and Assessment, 2022)
This research aimed to find out the improvement of students’ speaking fluency skill by using Assessment-for-learning approach. The sample of the research was the fourth semester students from UNISMUH MAKASSAR which consisted of 20 students. The sample was taken by using purposive sampling. The research findings showed that the fourth semester students of UNISMUH MAKASSAR had quite low score in pre-test. After treatment, their speaking skill was significantly improved. The result of the research was the mean score of speaking fluency obtained by the students pre-test was 44.75 and post-test was 70.25 with the significant score of the t-test is (0.00) or <(0.05). It means that there was significance difference between before and after giving the treatment. It indicated that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. It was concluded that the use Assessment-for-learning approach is effective in improving the students’ speaking fluency. Assessment-for-learning approach was one of the approach that can be considered in teaching English in order to help improved the students’ speaking fluency skill.